PERAN AUDITOR INTERNAL DALAM MENINGKATKAN EFEKTIFITAS TATA KELOLA PERUSAHAAN: STUDI KASUS SEKTOR KESEHATAN - Hia, Wiwin Veberlina; Miharja, Kasmanto; Damayanti, Novita; Angelina, Faustina Julia (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
This research explores the important role of internal auditors in enhancing the effectiveness of corporate governance in the healthcare services sector. Internal auditors play a crucial role in managing risks, ensuring compliance, and improving company performance, especially in the complex dynamics of the healthcare industry. In this study, a qualitative approach and case studies are used to evaluate the contributions of internal auditors to operational efficiency, regulatory compliance, as well as advice and solutions to achieve company's strategic objectives. This research find that internal auditors play a significant role in ensuring transparency, accountability, independence, and compliance in corporate governance. The results of this research provide valuable insights for stakeholders in the healthcare services sector, including managers, regulators, investors, and the public. This study also contributes significantly to the literature on corporate governance and internal audit practices in the context of the healthcare industry.Keywords: Internal auditor; Corporate governance; Healthcare services sector; PT Pelni Hospital; Hospital performance.